Cotidiano del estudiante de enfermería y obstetricia en el aprendizaje del cuidado a la gestante - Bernal Becerril, Martha Lilia (2014)
The educational process involves interaction between actors with dynamically changing communication and actions which involved desires, interests, motivations, expectations and interpretations. Objective: To describe and analyze the daily lives of nursing and midwifery students in learning care for pregnant. Theoretical approach was based on Lefebvre about the everyday; who says that people have to learn to adentrase his own benefit space to meet their needs and desires; in the model of critical social pedagogy of Freire argues that true education is praxis, reflection and action of man and Waldow who notes that care in teaching students must demonstrate caring behaviors, being autonomous, determined and responsible, using critical thinking. Qualitative descriptive study. were performed eight depth interviews. Selection of participants: technique "Snowball" to achieve "Saturation". Thematic Analysis of the Information that led to the construction of three categories: I) SYMBOLISM OF PREGNANT CARE with two subcategories: To participate in the miracle of life and Responsibility to family and community to achieve maternal welfare fetal; II) PRAXIS IN LEARNING with two subcategories: Acquisition of knowledge and skills vs knowledge construction and Learning theory and teaching practices of health personnel; and III) MULTIPLE CONSTRUCTION SENSE LEARNING two subcategories: Maintaining motivation and initiative and (In) enough time, space and resources for learning.